2008
DOI: 10.1002/lt.21449
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk for recurrent hepatocellular carcinoma after liver transplantation: Implications for surveillance studies and new adjuvant therapies

Abstract: The recurrence of hepatocellular carcinoma (HCC) is a major cause of mortality for patients transplanted with HCC. There currently exists no standard method for identifying those patients with a high risk for recurrence. Identification of factors leading to recurrence is necessary to develop an efficient surveillance protocol and address new potential adjuvant therapies. We Stepwise logistic regression identified 4 independent significant explant factors predictive of recurrence. Size of one tumor (Ͼ4.5 cm), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 21 publications
2
49
1
1
Order By: Relevance
“…The risk of recurrence in patients within the Milan criteria has been regularly reported to be 6% to 10%. 54 The inclusion of additional defining criteria such as pretransplant AFP levels or a risk factor analysis based on explant pathology findings should certainly be capable of reducing this risk. In the University of Alberta experience, although 2 of 4 of patients (50%) who were within the Milan criteria, had AFP levels > 400 ng/mL, and survived more than 6 months after liver transplantation experienced HCC recurrence, only 2 of 66 patients (3%) who were within the Milan criteria and had AFP levels < 400 ng/mL experienced recurrence.…”
Section: Question 3 What Is the Most Effective And Efficient Methods mentioning
confidence: 99%
“…The risk of recurrence in patients within the Milan criteria has been regularly reported to be 6% to 10%. 54 The inclusion of additional defining criteria such as pretransplant AFP levels or a risk factor analysis based on explant pathology findings should certainly be capable of reducing this risk. In the University of Alberta experience, although 2 of 4 of patients (50%) who were within the Milan criteria, had AFP levels > 400 ng/mL, and survived more than 6 months after liver transplantation experienced HCC recurrence, only 2 of 66 patients (3%) who were within the Milan criteria and had AFP levels < 400 ng/mL experienced recurrence.…”
Section: Question 3 What Is the Most Effective And Efficient Methods mentioning
confidence: 99%
“…Different systems to stage HCC have been created and validated, in various degrees. The American Joint Committee on Cancer revised the tumor, lymph nodes, and metastasis (TNM) classification of malignant tumors staging system and tumor satellites, and tumorspecific biomarkers [36] . Tumor differentiation and microvascular invasion are also substantial risks, but these features are not determined until after the evaluation of the explant.…”
Section: Stagingmentioning
confidence: 99%
“…Further evidence suggests that independent variables beyond the size of the tumor and total number of tumors may be linked to a more aggressive tumor biology, resulting in an increased chance of HCC recurrence post-transplant [39,79] . The diagnostic accuracy of MRI and CT has shown to be in the range of 45%-60% and for cases with lesions under stage, noted for 21%-43% [36] . This is likely because the relationship comparing imaging criterion and histopathology for cirrhotic hepatic explants needs further investigation.…”
Section: Recurrence Post Transplantationmentioning
confidence: 99%
“…Conversely, the degree of tumor cell differentiation is inversely associated with recurrent disease in that well-differentiated HCC is associated with decreased risk for recurrence. 39 Cillo and associates studied 48 patients with HCC in a prospective manner and found that patients with moderately to well-differentiated tumors had a 75% actuarial survival rate and 92% recurrence-free survival rate. 40 Thus, the degree of tumor differentiation and presence of vascular invasion before LT are predictors of post-LT HCC recurrence, but both are determined on explant pathology and are not as useful clinically during the selection process.…”
Section: Vascular Invasion/differentiation Of Hepatocellular Carcinomamentioning
confidence: 99%